Factors associated with postpartum weight retention among childbearing age women in selected health clinics in Seremban, Negeri Sembilan, Malaysia - Wan Zakaria, Wan Noor Fatehah (2018)
Postpartum weight retention (PWR) increases the risk of overweight and obesity in women of childbearing age. The aim of this study was to determine the factors associated with PWR in childbearing age women at selected health clinics in Negeri Sembilan at 6 months postpartum. The factors are socio-demographic characteristics, obstetrical factors, perinatal factors, lifestyle behaviours, dietary glycemic index (GI) and glycemic load (GL) and postpartum depression. This cross-sectional study was a part of Seremban Cohort Study (SECOST) and conducted at the Seremban, Ampangan and Senawang Health Clinics. The data collection was conducted over a period of 8 months, from January to August 2015. Ethical approval was obtained from the Ministry of Health Malaysia. A total of 226 respondents aged 21 to 46 years (31 ± 4.56 years) from Seremban, Ampangan and Senawang Health Clinics were recruited in this study. The response rate was 95%. The majority of respondents were Malay ethnic and married, employed and had attained tertiary level of education with monthly household income more than RM3000. The majority of the respondents had a vaginal delivery, multiparous and had a waist circumference more than 80 cm. The average of gestational weight gain (GWG) was 11 kg and 44.20% gained adequate GWG. The average of PWR was 2.59 ± 5.26 kg and 27.40% retained more 5 kg of weight at 6 months postpartum. Factors correlated significantly with PWR at 6 months were parity (r = - 0.137, p = 0.039), pre-pregnancy weight (r = -0.254, p= 0.001), pre-pregnancy Body Mass Index (BMI) (r = -0.297, p = 0.001), GWG (r = 0.529, p= 0.001), percentage of protein intake (r = 0.143, p = 0.032), intake of vitamin A (r = -0.131, p = 0.050), duration of exclusive breastfeeding at any times within 6 months (χ2 = 7.460, p = 0.024) and waist circumference at 6 months postpartum (F = 7.585, p = 0.045). Multiple linear regression analysis using a Stepwise method has shown five factors, namely; waist circumference at 6 months postpartum (Beta = 0.753, t = 9.900, p = 0.001); pre-pregnancy BMI (Beta = -0.718, t = -9.044, p = 0.001); GWG (Beta = 0.413, t =8.050, p = 0.001); duration of exclusive breastfeeding at any times within 6 months (Beta = -0.128, t = -2.726, p = 0.007); and height (Beta= -0.120, t = -2.423, p = 0.016) which were found to be the predictors for PWR. These predictors explained about 50.50 % of the variation in PWR according to the Stepwise Method (adjusted R2=0.505). In conclusion, high waist circumference, high GWG, low pre-pregnancy BMI, shorter duration of exclusive breastfeeding and short stature were associated with high PWR among childbearing age women.